2014
DOI: 10.3748/wjg.v20.i46.17476
|View full text |Cite
|
Sign up to set email alerts
|

Verification of gene expression profiles for colorectal cancer using 12 internet public microarray datasets

Abstract: A novel gene expression profile was associated with CRC and can potentially be applied to blood-based detection assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…In addition, we included microarray datasets obtained from our laboratory and published by Chang et al (2014b) ( , , , , , , , , , , , and ), which included 519 adenocarcinoma cases and 88 normal mucosa control cases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we included microarray datasets obtained from our laboratory and published by Chang et al (2014b) ( , , , , , , , , , , , and ), which included 519 adenocarcinoma cases and 88 normal mucosa control cases.…”
Section: Methodsmentioning
confidence: 99%
“…The use of pooled GEO studies was secondary because only the microarray data were available. Previous studies have proposed that testing 55 genes in any experimental model is beneficial for colon cancer biology ( Chang et al, 2014a ; Chang et al, 2014b ; Chu et al, 2014a ; Chu et al, 2014b ). Therefore, in the present study, functional pathways related to the tumorigenesis of CRC were evaluated using GSEA software version 2.07.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokines such as IL12A, IL1R1 and IL2RB, which are identified in our gene signature, play a major role as inflammatory mediators and are reported to greatly contribute as one of the factors in CRC development [40]. A study reported a seven-gene expression profile based on 12 gene expression omnibus (GEO) datasets indicated that IL2RB is strongly associated with CRC [41]. Mutations in NKD1 also lead to the activation of Wnt signaling pathways and the promotion of cell proliferation in CRC [33].…”
Section: Discussionmentioning
confidence: 99%
“…Expression data of human tumor tissues were downloaded from GSE2109 ( http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE2109 ), which consisted of 2158 arrays from solid tumors. When combining datasets from different studies, it is necessary to standardize data to remove batch effect [ 19 , 20 ]. Therefore, we kept genes available on all arrays, and performed the between-study normalization by “ComBat” function in R.…”
Section: Methodsmentioning
confidence: 99%